2003
DOI: 10.1034/j.1601-5037.2003.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of modified Bass technique with normal toothbrushing practices for efficacy in supragingival plaque removal

Abstract: The results show that a particular toothbrushing technique as modified Bass method is significantly superior to normal toothbrushing practices in supragingival plaque removal. The introduction of a specific toothbrushing technique, such as modified Bass technique represents an important improvement in the oral hygiene of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
88
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 18 publications
7
88
0
2
Order By: Relevance
“…The results reported by Poyato-Ferrera et al [4] concur with those of the current study, in that the modified Bass technique was also an efficacious method for removing plaque. Indeed, Poyoto-Ferrera et al [4] reported that the modified Bass technique was the optimal method for brushing teeth in terms of plaque removal, and the current study was similar in that this method again yielded the most significant differences in plaque scores after brushing.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results reported by Poyato-Ferrera et al [4] concur with those of the current study, in that the modified Bass technique was also an efficacious method for removing plaque. Indeed, Poyoto-Ferrera et al [4] reported that the modified Bass technique was the optimal method for brushing teeth in terms of plaque removal, and the current study was similar in that this method again yielded the most significant differences in plaque scores after brushing.…”
Section: Discussionsupporting
confidence: 81%
“…Tooth brushing is an essential element of an effective plaque control program, and we hypothesized that attaining optimal oral health would depend on the efficacy of the method used and the ease of carrying out the procedure. It is well established that, in children, tooth brushing is still the most efficient way of removing plaque in the long term [3] and normal tooth brushing is sufficient to prevent bacterial plaque [4]. However, when we buy a toothbrush, we rarely receive special instructions on how to use it, except where the manufacturer might include some instruction in the packaging.…”
mentioning
confidence: 99%
“…The results reported by Poyato-Ferrera et al [4] concur with those of the current study, in that the modified Bass technique was also an efficacious method for removing plaque. Indeed, Poyoto-Ferrera et al [4] reported that the modified Bass technique was the optimal method for brushing teeth in terms of plaque removal, and the current study was similar in that this method again yielded the most significant differences in plaque scores after brushing. The results of the current study contrast with the those of Aria et al, [9] who reported that the modified Bass technique was less effective for plaque removal than the modified Stillman's technique; however, our findings are in agreement with those of Saghazadeh et al [13] who reported that, when plaque removal was compared between six different brushing techniques, the modified Bass technique was more effective than the modified Stillman's technique.…”
Section: Discussionsupporting
confidence: 81%
“…Participants in the test group were given instruction on oral hygiene care, including toothbrushing with the modified Bass technique (33) and interdental cleaning, and underwent scaling and root planing (SRP), which was performed under local anesthesia by a trained dentist (Z.A.) using an ultrasonic scaler (SATELEC P5 Newtron XS, Cambridge, UK) and Gracey curettes (Hu-Friedy) at a single appointment.…”
Section: Nsptmentioning
confidence: 99%